Services oriented management of spatial moving objects - Jingnong Weng; Yang Wang (2010 18th International Conference on Geoinformatics, 2010)
With the rapid development of information technology, research on spatial moving objects has become popular in the area of information management. Based on discussions to fundamental question of moving objects and analysis of the survey in related research fields, an approach of services oriented management of spatial moving objects in three dimension GIS system is presented in this paper, which include the discussion of the basic attributes, spatial characteristics, patterns of behaviors and relationships between each other of moving objects and their models, the data mining of mass moving objects data based on the services oriented idea and architecture, the establishment of the moving objects' service models, key technologies and its solutions, etc.